Robotic hip-disarticulation prosthesis: evaluation of prosthetic gaits in a non-amputee individual. (2nd January 2020) - Ueyama, Yuki; Kubo, Tsutomu; Shibata, Masaaki
Abstract : This is the first report regarding the application of a robotic prosthesis for hip-disarticulation amputees. Hip-disarticulation prostheses (HDPs) are used by amputees with either an amputation or anomaly at or close to the hip joint. Robotics can be beneficial in such cases, as these individuals have reduced levels of motor function compared to other amputees and have limited mobility. We developed a robotic HDP, and analysed the gaits of a non-amputee using the robotic and non-powered dummy HDPs. The results imply that a robotic HDP may induce proper gait and maintain the burdens of the prosthetic and non-prosthetic limbs symmetrically. GRAPHICAL ABSTRACT: